2016
DOI: 10.1044/2016_jslhr-l-15-0107
|View full text |Cite
|
Sign up to set email alerts
|

Processing Binding Relations in Specific Language Impairment

Abstract: Purpose: This sentence processing experiment examined the abilities of children with specific language impairment (SLI) and children with typical language development (TD) to establish relations between pronouns or reflexives and their antecedents in real time. Method: Twenty-two children with SLI and 24 age-matched children with TD (7;3-10;11 [years;months]) participated in a cross-modal picture priming experiment to determine whether they selectively activated the correct referent at the pronoun or reflexive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The CMPT has often been used to investigate the processing of lexical ambiguity (e.g., Klepousniotou, 2002; Onifer & Swinney, 1981; Swinney, 1979; Swinney, Love, Walenski & Smith, 2007; Tabossi, 1988) and syntactic dependencies, e.g., filler-gap dependencies (Love & Swinney, 1996; Love & Swinney, 2007; Marinis & van der Lely, 2007; Nicol, 1993; Felser & Roberts, 2007; Roberts, Marinis, Felser & Clahsen, 2007); object scrambling (Clahsen & Featherston, 1999; Nakano, Felser & Clahsen, 2002); and reference of pronouns and reflexives (McKee, Nicol & McDaniel, 1993; Nicol & Swinney, 1989; Schwartz, Hestvik, Seiger-Gardner & Almodovar, 2016).…”
Section: Cross-modal Priming: the Methodsmentioning
confidence: 99%
“…The CMPT has often been used to investigate the processing of lexical ambiguity (e.g., Klepousniotou, 2002; Onifer & Swinney, 1981; Swinney, 1979; Swinney, Love, Walenski & Smith, 2007; Tabossi, 1988) and syntactic dependencies, e.g., filler-gap dependencies (Love & Swinney, 1996; Love & Swinney, 2007; Marinis & van der Lely, 2007; Nicol, 1993; Felser & Roberts, 2007; Roberts, Marinis, Felser & Clahsen, 2007); object scrambling (Clahsen & Featherston, 1999; Nakano, Felser & Clahsen, 2002); and reference of pronouns and reflexives (McKee, Nicol & McDaniel, 1993; Nicol & Swinney, 1989; Schwartz, Hestvik, Seiger-Gardner & Almodovar, 2016).…”
Section: Cross-modal Priming: the Methodsmentioning
confidence: 99%
“…However, the criteria used to arrive at this determination vary considerably across experiments (see Simmons et al, 2011) . In the Journal of Speech, Language, and Hearing Research alone, outliers have been defined as responses that fall more than two standard deviations beyond the mean response for each item (Krestar & McLennan, 2019) , more than three standard deviations from a participant's mean response time for each task (Strand et al, 2018) , more than three standard deviations from the mean response time for the block (Iuzzini-Seigel, 2021) , more than three standard deviations from the by-participant, by-block mean (Earle & Ullman, 2021) , above or below a stable threshold (Schwartz et al, 2016) , or for unspecified reasons. These extreme values are sometimes removed (as in the studies above), or sometimes replaced with a fixed value (e.g., values greater than two standard deviations above the mean replaced with the value two standard deviations above the mean; Smith, 2011) .…”
Section: Why Preregistration Benefits Speech Language and Hearing Res...mentioning
confidence: 99%
“…There are a few applications that the experimenter can run with E-Prime, including carrying out the experiment, collecting results, conducting some basic data analysis and exporting data. A considerable amount of literature has revealed that the application of E-Prime is useful for experimentation, notably for psychology studies and studies focusing on syntactic SLI, and researchers have widely investigated its probe accuracy and response time or reaction time (RT) for syntactic and lexical processing or even procedural learning ( 12 14 ). Furthermore, many attempts have been made by researchers to investigate real-time syntactic processing among participants syntactic SLI.…”
Section: Introductionmentioning
confidence: 99%